2004
DOI: 10.1111/j.0007-1013.2004.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perceptions toward the use of the digital library in weekly web‐based distance learning assignments portion of a hybrid programme

Abstract: Students' perceptions toward the use of the digital libraryBritish Journal of Educational Technology Students' perceptions toward the use of the digital library in weekly web-based distance learning assignments portion of a hybrid programme Alex Koohang Dr Alex Koohang is an associate professor and director of undergraduate program in the School of Information Studies at University of Wisconsin-Milwaukee, USA. Dr Koohang has designed, developed, and implemented various traditional, non-traditional, hybrid, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 7 publications
3
32
0
2
Order By: Relevance
“…This study shows student's gender either male or female, that the number of male students is higher than the number of female students. This confirms the finding of Koohang's (2004) study regarding gender is that boys were more inclined to use the blended learning environment than girls. To answer the questions that determined if the students have studied English course as BL mode.…”
Section: Resultssupporting
confidence: 89%
“…This study shows student's gender either male or female, that the number of male students is higher than the number of female students. This confirms the finding of Koohang's (2004) study regarding gender is that boys were more inclined to use the blended learning environment than girls. To answer the questions that determined if the students have studied English course as BL mode.…”
Section: Resultssupporting
confidence: 89%
“…This study is supported by the results of research conducted on students' perceptions of the use of digital libraries as part of the Hybrid Learning task [9]. The study was conducted in high school in the Mildwest United States to 154 students.…”
Section: Discussionmentioning
confidence: 63%
“…What literature exists provides an incomplete and even contradictory picture of student engagement with online library materials. While Koohang (2004) found that male students were more likely to self-report high levels of confidence and satisfaction engaging with the online library, a very early study by Alexander and Smith (2001) showed that more women than men expressed a preference for online library instruction. Jowitt's study in New Zealand (2008) indicated that the population of students self-selecting to use library-produced podcasts to learn library skills was largely female.…”
Section: Literature Reviewmentioning
confidence: 98%